SYSTEM OF IMPROVING PSYCHOLOGICAL PREPARATION OF STUDENTS FOR PROFESSIONAL ACTIVITY - Tashnazarovna, Nazarova Ozoda (International Journal of Psychosocial Rehabilitation, 2020)
The article is aimed at studying the system of improving the psychological readiness of students for professional activities. It also analyzes a number of scientific sources on general methodological and theoretical issues related to career choice, career guidance, understanding and definition of professional identity. The research focuses on the specific characteristics of individuals with motives for action in three areas. Self-direction. This is manifested in the predominance of motives for high authority, in the desire to be able to fully manage and analyze the qualities of one’s own personality. People-centeredness is a feature of the pill that seeks to be close and warm to people in any situation. Activity-oriented - an interest in solving problems related to work, the desire to perform the task as carefully as possible, such a person quickly gets bored of the usual way of organizing work and, therefore, requires constant change and improvement of the work process. In the process of professional formation and development of students, the desire for self-recognition by others in terms of "self-direction", sensitivity, spiritual richness, intelligence and intelligence; Ability to interact with people in a "people-oriented" way, the tendency to establish warm relationships, easy mastering of professions; In the field of "activity-oriented" scientifically studied the formation of thorough performance, quick adaptability to situations, confidence in work and other qualities